The evolution of performance indicators in high-intensity and high-speed training for boys aged 10 to 13, with varying levels of physical activity - Khuasin, C.; Yindon, N.; Vrublevskiy, E. P. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to discern the effects of age on the performance metrics of speed and power-speed fitness in boys aged 10 to 13, with varying levels of physical activity.